The Adaptation to Climate Change Portrayed Through Al Gore's Character in An Inconvenient Sequel:Truth to Power Film(An Ecocriticism Study) - Novita Sari; Singgih Daru Kuncara; Fatimah M (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2023)
In industrialization era, human activities have a global impact on the environment. Natural phenomena begin to occur, one of which is climate change. Rising sea-levels, warming earth temperatures, and air pollution are the actual impacts of climate change. The study aimed to explain how climate change is portrayed in An Inconvenient Sequel: Truth to Power Film. In addition, this study also tried to investigate the adaptations carried out by Al Gore as the main character in responding to climate change. This study is descriptive qualitative research. The study used ecocriticism theory (By Garrard, 2004) to explain the representation of climate change and the adaptation of the main character to climate change. Data obtained from An Inconvenient Sequel: Truth to Power Film by Bonni Cohen and Jon Shenk was released in 2017. The results of the data analysis showed the representation of climate change in the film through issues covering three aspects, apocalypse, pollution, and earth. These three aspects significantly impact human life, particularly health, economy, and environment. In addition, adaptations made by the main character in responding to climate change can be analyzed through environmentalism and deep ecology. The main character responded to environmentalism by building self-awareness of environmental concerns, and he created a training program to build awareness of human beings. Meanwhile, in deep ecology, he suggested switching to renewable energy to meet human energy needs to be more environmentally friendly and reduce the effects of greenhouse gases and pollution.